2020
DOI: 10.1111/bju.15064
|View full text |Cite|
|
Sign up to set email alerts
|

Robotic partial nephrectomy vs minimally invasive radical nephrectomy for clinical T2a renal mass: a propensity score‐matched comparison from the ROSULA (Robotic Surgery for Large Renal Mass) Collaborative Group

Abstract: Objective To compare outcomes of minimally invasive radical nephrectomy (MIS‐RN) and robot‐assisted partial nephrectomy (RAPN) in clinical T2a renal mass (cT2aRM). Patients and Methods Retrospective, multicentre, propensity score‐matched (PSM) comparison of RAPN and MIS‐RN for cT2aRM (T2aN0M0). Cohorts were PSM for age, sex, body mass index, American Society of Anesthesiologists (ASA) class, clinical tumour size, and R.E.N.A.L. score using a 2:1 ratio for RN:PN. The primary outcome was disease‐free survival (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
28
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 35 publications
3
28
1
1
Order By: Relevance
“…Bradshaw et al . also showed no significant differences in major complications (CDC ≥3) for PN versus RN in large RCC (5.3% vs 2.3%, P = 0.063) in their recently published propensity score‐matched comparison of minimally invasive RN versus robot‐assisted PN in cT2a renal masses 26 . In the present study, we were not able to show any influence of the tumor complexity or other investigated tumor, as well as patient‐related parameters, on the occurrence of higher‐grade complications.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Bradshaw et al . also showed no significant differences in major complications (CDC ≥3) for PN versus RN in large RCC (5.3% vs 2.3%, P = 0.063) in their recently published propensity score‐matched comparison of minimally invasive RN versus robot‐assisted PN in cT2a renal masses 26 . In the present study, we were not able to show any influence of the tumor complexity or other investigated tumor, as well as patient‐related parameters, on the occurrence of higher‐grade complications.…”
Section: Discussionmentioning
confidence: 92%
“…In the multivariable analysis for CKD, the surgical approach was an independent factor in favor of PN compared with RN (OR 51.071, 95% CI 3.570–730.5899, P = 0.004). Other authors also found that PN was associated with better postoperative renal function, with reported higher postoperative eGFR and a lower likelihood of postoperative onset of CKD 23,26,27 . As a result of better preservation of renal function, PN was observed to achieve a better health‐related and overall quality of life 28 .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…For instance, a similar analysis focused on cT2a masses was recently published by Bradshaw et al ., who found that robot‐assisted PN showed similar oncological outcomes and morbidity profile to minimally invasive RN, while lowering the likelihood of a de novo chronic kidney disease 2 . This was possible by means of a retrospective, multicenter, propensity score‐matched comparison within the Robotic Surgery for Large Renal Mass consortium.…”
mentioning
confidence: 99%
“…To date, robot‐assisted partial nephrectomy (RAPN) is becoming the standard procedure for localized RCC instead of open or laparoscopic technique. Although RAPN was recommended for patients with small RCC, the adaptation of RAPN was expanded to more than cT2 RCC, because of its safety and improvement of surgeons’ techniques 2 . The authors showed PN to be superior to radical nephrectomy for both renal function preservation and complications.…”
mentioning
confidence: 99%